Trinidad. Coconut Picking - (:unkn) unknown (Stephens Ltd., Trinidad, 2009)
A picture of a man climbing a coconut tree using a rope to assist.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm; Agriculture; Working class; Tree climbing